NEW DATA ON CRETACEOUS FLYING REPTILES (PTEROSAURIA) FROM RUSSIA, KAZAKHSTAN, AND KYRGYZSTAN - Averianov A.O. (My University, 2004)
New and previously unpublished finds of pterosaurian bones are described from the Cretaceous of Russia, Kazakhstan, and Kyrgyzstan. The following taxa are determined: Pterodactyloidea indet. (distal fragment of femur; Kylodzhun locality, Kyrgyzstan; Albian); a very large Pterodactyloidea indet. (distal fragment of a second wing phalanx; Pavlovsk, Voronezh Region; Cenomanian); Ornithocheiridae indet. (distal fragment of the fourth metacarpal; Lebedinskii Quarry, Belgorod Region; Albian-Cenomanian; fragmentary maxilla; Sinen'kie locality, Saratov Region; Lower Cenomanian; fragmentary pelvis, femur, and sacral vertebrae from the same animal; Saratov, Russia; Cenomanian); and Azhdarchidae gen. et sp. indet. (jugal and a fragmentary cervical vertebra; Shakh-Shakh locality, Kazakhstan; Santonian-Campanian).
Keywords: Pterosauria; Pterodactyloidea; Ornithocheiridae; Azhdarchidae; Cretaceous; Russia; Kazakhstan; Kyrgyzstan; Mesozoic::Cretaceous; Мезозой::Меловая